Multi-layer composite anti-wrinkle swelling adhesive tape

By adopting multi-layer composite structure and vacuum evaporation technology in the swelling tape of lithium battery, the problems of uneven thickness, poor stiffness and insufficient penetration capacity of the existing tape are solved, and efficient gap filling and extended lithium battery life are achieved.

CN222250550UActive Publication Date: 2024-12-27JIANGXI RUIGUAN NEW MATERIALS CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202420477279.1
Authority / Receiving Office
CN · China
Patent Type
Utility models(China)
Current Assignee / Owner
Filing Date
2024-03-12
Publication Date
2024-12-27
Estimated Expiration
2034-03-12

AI Technical Summary

Technical Problem

In the assembly of lithium battery, existing swelling tapes have problems such as poor thickness uniformity, easy to produce bubbles, poor stiffness, poor permeability to electrolyte, and micro gaps and bubbles between resin and substrate, resulting in short life and safety of lithium batteries. Hidden danger.

Method used

Using a multi-layer composite anti-wrinkle swelling tape structure, including PET or other high-strength substrate layer, adhesive coating, barrier layer, TPU film and acrylic pressure-sensitive adhesive layer, ceramic barrier layer is formed by vacuum deposition of silica, combined with Solvent-free composite process and transfer coating process ensure high barrier properties, stiffness and tensile strength of the tape.

Benefits of technology

The tape is achieved with high uniformity, low bubbles, good stiffness and high barrier properties, ensuring that the gap filling accuracy reaches the micron level, extending the life of lithium batteries, reducing production costs, and improving safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN222250550U_ABST
    Figure CN222250550U_ABST
Patent Text Reader

Abstract

The utility model relates to a multi-layer composite anti-wrinkle swelling adhesive tape which sequentially comprises a base material layer, a tackifying coating coated on the base material layer, a barrier layer bonded on the tackifying coating, a TPU (Thermoplastic Polyurethane) film arranged on the barrier layer and an acrylic acid pressure-sensitive adhesive layer bonded on the TPU film, the release paper layer is adhered to the acrylic acid pressure-sensitive adhesive layer, and the barrier layer is made of silicon dioxide. According to the multi-layer composite anti-wrinkle swelling adhesive tape provided by the utility model, the stripping force of the multi-layer composite anti-wrinkle swelling adhesive tape is ensured, and the multi-layer composite anti-wrinkle swelling adhesive tape is free from delamination, free from bubbling, smooth and stiff in product, excellent in high-barrier property and good in high-temperature resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The utility model relates to the technical field of swelling tape materials used in the lithium battery industry, in particular to a multi-layer composite anti-wrinkle swelling tape. Background Art

[0002] When assembling cylindrical lithium batteries, there will be a pre-designed installation gap between the battery cell and the shell. If the gap reserved for the installation is too large, the battery cell will move when it is subjected to external impact, affecting the normal operation life of the lithium battery and posing a safety hazard. If the reserved gap is too small, it will make installation difficult. Therefore, in the lithium battery manufacturing industry, sol tape is usually used. When a gap is reserved between the battery cell and the shell and is soaked in electrolyte, the area and volume of the sol tape will swell to fill the reserved gap, thereby preventing the battery cell from moving when it is subjected to external impact.

[0003] In the prior art, the swelling tape generally includes a swelling resin layer, a substrate layer as a supporting skeleton, a pressure-sensitive adhesive layer, and a release film. After being heated or in contact with an electrolyte, the swelling resin layer will expand in length, width, area, and volume, thereby filling the installation gap reserved in the battery, and further fixing the battery cell and the shell into one body, achieving the actual test conditions.

[0004] However, the swelling tapes on the market have the following defects. Since the swelling resin layer uses TPU resin, and the substrate layer is made of several typical materials made by coating or laminating (compounding) processes. Therefore, during the laminating or compounding process, the substrate needs to undergo high-temperature heating and stretching in a drying oven, which will cause deformation after heating, resulting in poor thickness uniformity of the finished product, and easy generation of tiny bubbles, resulting in low peeling force. Therefore, it is necessary to use a high-temperature resistant substrate, which leads to high requirements for the material of the substrate layer, and also leads to increased costs, and the market application is also limited. Another defect is that the swelling resin used in the swelling resin layer is relatively soft and has poor stiffness. After it comes into contact with certain acidic or alkaline substances in the electrolyte, it will dissolve and corrode, resulting in local shrinkage of the swelling layer and abnormal appearance deformation. The swelling rate is difficult to reach the design expectation of the swelling rate, and it is impossible to achieve tight filling of the installation gap.

[0005] In view of the above defects, a common method in the lithium battery manufacturing industry is to set a support layer between the swelling resin layer and the pressure-sensitive adhesive layer, for example, using a PE substrate as a support substrate and adding titanium dioxide therein. The good mechanical properties (strength, hardness) and chemical stability of titanium dioxide to acid and alkali solutions are used to support the swelling resin layer and improve the stiffness of the swelling agent tape to the electrolyte, thereby avoiding the problem of shrinkage of the swelling resin layer due to dissolution. Although this method has a certain effect on improving the deformation and stiffness performance of the tape, the tape has poor permeability to the electrolyte and poor ability to resist the shrinkage and surface deformation of the swelling layer. In addition, it cannot solve the problem of micro-gaps and bubbles between the resin and the substrate, which are not conducive to ensuring the normal operation and life of the lithium battery and also pose a major safety hazard. Utility Model Content

[0006] In view of this, the utility model provides a multi-layer composite anti-wrinkle swelling tape and a preparation method thereof to meet industrial needs and solve the above-mentioned problems.

[0007] A multi-layer composite anti-wrinkle swelling tape comprises, in sequence, a substrate layer, an adhesion-promoting coating layer coated on the substrate layer, a barrier layer bonded to the adhesion-promoting coating layer, a TPU film vapor-deposited on the barrier layer, an acrylic pressure-sensitive adhesive layer bonded to the TPU film, and a release paper layer adhered to the acrylic pressure-sensitive adhesive layer, wherein the barrier layer is made of silicon dioxide.

[0008] Furthermore, the substrate layer is one of PET, PA, PI, PC, PS, PE, PP, and EVA.

[0009] Furthermore, the barrier layer is a silicon dioxide layer formed by vacuum evaporation.

[0010] Furthermore, the barrier layer is made by vacuum evaporation, and the evaporated material is a non-metallic oxide or sulfide that can have a barrier effect on the electrolyte.

[0011] Furthermore, the adhesion-enhancing coating is a water-based coating, and the water-based coating is made of polyethyleneimine or thermosetting polyurethane resin.

[0012] Furthermore, the pressure-sensitive adhesive layer is disposed on the substrate layer by transfer coating.

[0013] Furthermore, the pressure-sensitive adhesive layer is acrylic pressure-sensitive adhesive.

[0014] Furthermore, the adhesion-promoting coating and the barrier layer are compounded together at room temperature and then aged at room temperature.

[0015] Compared with the prior art, the multi-layer composite anti-wrinkle swelling tape provided by the utility model has the following beneficial effects:

[0016] 1. One of the characteristics of the multi-layer composite anti-wrinkle swelling tape: the substrate layer 10 is combined with the adhesion-enhancing coating resin, and the polyethyleneimine water-based resin is coated on the PET film, so as to ensure the uniformity of the surface performance of the PET film. At the same time, a thinner film material is used as the substrate layer 10 of the product, so as to ensure the peeling force of the multi-layer composite anti-wrinkle swelling tape, no delamination, no blistering, product flatness and stiffness, as well as high barrier and high temperature resistance.

[0017] 2. The second characteristic of the multi-layer composite anti-wrinkle swelling tape: The solvent-free process is a process of compounding and natural maturation at room temperature. There is no heating of the functional layers and the addition and evaporation of the solvent. The uniformity of the thickness can be improved from the millimeter level to the micron level, so that the filling accuracy of the lithium battery gap can reach the micron level. At the same time, the selection range of the substrate layer 10 is expanded, greatly expanding the application range of the product.

[0018] 3. The vacuum coating of inorganic compounds represented by silicon dioxide, i.e. the barrier layer 12, forms a ceramic coating that does not react to the electrolyte, limits the penetration space of the electrolyte, and avoids the deformation and shrinkage problems caused by the dissolution of the substrate layer 10. The thickness of the barrier layer 12 is preferably controlled at 70 to 350 nm, and the tape can maintain a swelling rate of ≥140% of the area to ensure tight filling of the gap during use.

[0019] 4. The room temperature solvent-free composite technology and process adopted by the utility model can meet the diversified swelling needs by adding TPU film to ensure excellent stiffness and tensile strength, and adding adhesion coating process and silicon dioxide ceramic film evaporation process to prevent electrolyte penetration, compared with the existing swelling tape technology process based on coating process. It is more flexible, has higher production efficiency and processing precision, and therefore has obvious cost advantages. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a schematic structural diagram of the multi-layer composite anti-wrinkle swelling tape provided by the utility model. DETAILED DESCRIPTION

[0021] The following is a further detailed description of the specific embodiments of the present invention. It should be understood that the description of the embodiments of the present invention herein is not intended to limit the protection scope of the present invention.

[0022] like Figure 1As shown, it is a schematic diagram of the structure of a multi-layer composite anti-wrinkle swelling tape provided by the utility model. The multi-layer composite anti-wrinkle swelling tape comprises a substrate layer 10, an adhesion-promoting coating layer 11 coated on the substrate layer 10, a barrier layer 12 bonded to the adhesion-promoting coating layer 11, a TPU film 13 disposed on the barrier layer 12, an acrylic pressure-sensitive adhesive layer 14 bonded to the TPU film 13, and a release paper layer 15 adhered to the acrylic pressure-sensitive adhesive layer 14. It is conceivable that the multi-layer composite anti-wrinkle swelling tape may also include other functional layers, such as a protective film, a label layer, etc., which are well known to those skilled in the art and will not be described in detail here.

[0023] The substrate layer 10 can not only select a substrate with high strength and high temperature resistance, such as PET, PA, PI, PC, PS, etc., but also a soft substrate, such as PE, PP, EVA, PP, etc. In the present embodiment, the substrate layer 10 is a PET film, which can improve the stiffness and tensile strength of the product. Taking advantage of the good stiffness and relatively good tensile strength physical properties of PET, it is used as the supporting material of the multi-layer composite anti-wrinkle swelling tape of the utility model. The thickness range of the PET film used in the substrate layer 10 is 12 to 25 μm, and a black TPU film with a thickness of 20 μm is preferred. The surface of the PET film is used as the coating surface during the solvent-free composite process, and contacts the solvent-free adhesive together with the water-based tackifying resin layer. After the solvent-free composite process, it becomes a coil of the composite film, and after the room temperature aging process, it becomes a composite semi-finished roll film. The usual solvent-free composite process arrangement is to use TPU film with higher tensile strength as the coating film. PET is a single chemically treated film with chemical treatment on the lower surface to ensure the necessary wetting tension ≥52 for composite.

[0024] The adhesion-promoting coating 11 can be a primer material applied on one side of the substrate layer 10 by a coating machine. The primer material used to apply the adhesion-promoting coating 11 can be a water-based primer, and the adhesion-promoting coating 11 can be made of a composition of polyethyleneimine or a thermosetting polyurethane resin and polyisocyanate. During coating, the general coating dry weight is 0.03-0.08 g / m 2 , solid content 0.7~5.6%, dry weight 0.05~0.07g / m 2 , thickness 0.01~0.04μm. The adhesion primer resin of polyethyleneimine aqueous solution or polyurethane resin aqueous solution applied by the coating machine has a very thin thickness of ≤1μm, and the dry glue amount of the film is usually 0.7~0.98g / m 2 Polyethyleneimine is a representative resin with excellent swelling rate. It is used as one of the raw materials in the form of roll film before compounding the finished product. According to different needs, its surface can be pre-coated with defoaming agent, leveling agent and other additives to increase surface function.

[0025] The barrier layer 12 is deposited on the TPU film 13 by vacuum evaporation. The evaporated material is a non-metallic oxide or sulfide that can act as a barrier to the electrolyte, such as silicon dioxide or titanium dioxide. In this embodiment, the evaporated material is silicon dioxide. In order to make the barrier layer 12 have the same tension as the substrate layer 10, the wetting tension of the substrate layer 10 should be greater than or equal to 52. It is deposited on the upper surface of the TPU film 13 through vacuum coating, and is bonded to the surface by compounding with the adhesion-enhancing coating 11 on the lower surface of the substrate layer 10. According to testing, the water vapor permeability of the coating, i.e. the barrier layer 12, is ≤12g / m 2 ·24h, oxygen permeability 1400≤cm / ㎡·24h·0.1MPa, so as to limit the penetration of the control electrolyte. The vacuum coating of inorganic compounds represented by silicon dioxide forms a ceramic coating that does not react to the electrolyte, which limits the penetration space of the electrolyte and avoids the problem of deformation and shrinkage caused by the dissolution of the substrate layer 10. The thickness of the barrier layer 12 is preferably controlled at 70-350nm, and the multi-layer composite anti-wrinkle swelling tape can maintain a swelling rate of ≥140% of the area to ensure the tight filling of the gap during use. When in use, the barrier layer 12 acts as a high barrier layer with unidirectional permeability to the electrolyte, so it can completely swell the TPU film 13, that is, the TPU film, so that the swelling rate is high, and uniform swelling can be ensured, avoiding the electrolyte from penetrating through the TPU gap to the surface of the substrate layer 10 to form microbubbles, and the interface peeling force between the functional layers is reduced. During evaporation, a continuous vacuum coating machine is used to evaporate the barrier layer 12, that is, the silicon dioxide coating, on the upper surface of the TPU film 13. Specifically, the silicon dioxide powder is placed in a crucible at the bottom of the vacuum chamber and heated. It is heated by a large current and evaporated into a vapor state. Under vacuum conditions, the evaporation temperature is required to be 1200-1600°C. In this embodiment, the coating thickness range is 70-350nm, and the film is rolled up after continuous evaporation. In addition, a certain amount of nitrogen is filled in the chamber during the vacuum coating process to protect the substrate layer 10 and the swelling layer 13 from deformation.

[0026] The TPU film 13 is made of a TPU film that has a swelling function for electrolyte. The multi-layer composite anti-wrinkle swelling tape product usually has a thickness of ≤45μm. The material of the TPU film 13 is a polymer resin represented by TPU, and the thickness usually ranges from 15 to 50μm. It reacts with the electrolyte to form swelling. After it is dissolved, PET provides the necessary stiffness to ensure that it does not shrink and can maintain a swelling rate of ≥130% of the area. As a swelling material, it has the characteristics of expanding in length, width, thickness (volume) after dissolving the electrolyte.

[0027] During the preparation process, the barrier layer 12 is firstly vapor-deposited on the TPU film 13, and then the adhesion-enhancing coating 11 is coated on the substrate layer 10. Finally, the barrier layer 12 and the adhesion-enhancing coating 11 are bonded together at room temperature without heating and in a solvent-free condition. During the composite process, no solvent is added, and the two substrates and the adhesive are not heated. Therefore, the product is free of bubbles and tiny pores, etc., which effectively solves the problem of product deformation.

[0028] The pressure-sensitive adhesive layer 14 uses acrylic pressure-sensitive adhesive as the adhesive to adhere to the battery core and fix the position. The adhesive layer is required to be as thin as possible and resistant to high temperature while ensuring the peeling force. For example: in the battery electrolyte at 85°C, the swelling resin represented by TPU or EVA is swollen by the electrolyte to produce an expanded body with enlarged area and volume, thereby filling the installation gap. Therefore, a pressure-sensitive adhesive coating with strong adhesion and temperature resistance is required. In order to protect the flatness of the composite layer with swelling function, the utility model adopts a special transfer process, that is, the pressure-sensitive adhesive is coated on a conventional film by a coating machine, and then attached to the surface of the substrate layer 10 of the swelling tape on the other side of the swelling layer 13 at room temperature by transfer, forming an adhesive layer with greater peeling force. The pressure-sensitive adhesive layer 14 can be made of acrylic resin material. The pressure-sensitive adhesive transfer coating process is adopted to reduce the one-time heating coating process of the conventional process for producing swelling tapes, thereby reducing the probability of deformation and bubble problems of the swelling tape, improving product performance and providing quality assurance, and expanding the scope of application. It can meet the needs of products with different swelling rates and different mechanical properties, and can be used in home appliances, automobiles, machinery, instruments, batteries, decoration and other industries. Specifically, it can be used for gap filling in home appliances, automobiles, lithium batteries, instruments and various mechanical parts under specific environments.

[0029] The release film 15 can be a transparent PET substrate release film with a thickness of 19 μm, which has the performance to ensure complete peeling of the multi-layer composite anti-wrinkle swelling tape. It is a prior art and will not be described in detail here.

[0030] Compared with the prior art, the multi-layer composite anti-wrinkle swelling tape provided by the utility model has the following beneficial effects:

[0031] 1. One of the characteristics of the multi-layer composite anti-wrinkle swelling tape: the substrate layer 10 is combined with the adhesion-enhancing coating resin, and the polyethyleneimine water-based resin is coated on the PET film, so as to ensure the uniformity of the surface performance of the PET film. At the same time, a thinner film material is used as the substrate layer 10 of the product, so as to ensure the peeling force of the multi-layer composite anti-wrinkle swelling tape, no delamination, no blistering, product flatness and stiffness, as well as high barrier and high temperature resistance.

[0032] 2. The second characteristic of the multi-layer composite anti-wrinkle swelling tape: The solvent-free process is a process of compounding and natural maturation at room temperature. There is no heating of the functional layers and the addition and evaporation of the solvent. The uniformity of the thickness can be improved from the millimeter level to the micron level, so that the filling accuracy of the lithium battery gap can reach the micron level. At the same time, the selection range of the substrate layer 10 is expanded, greatly expanding the application range of the product.

[0033] 3. The vacuum coating of inorganic compounds represented by silicon dioxide, i.e. the barrier layer 12, forms a ceramic coating that does not react to the electrolyte, limits the penetration space of the electrolyte, and avoids the deformation and shrinkage problems caused by the dissolution of the substrate layer 10. The thickness of the barrier layer 12 is preferably controlled at 70 to 350 nm, and the tape can maintain a swelling rate of ≥140% of the area to ensure tight filling of the gap during use.

[0034] 4. The room temperature solvent-free composite technology and process adopted by the utility model can meet the diversified swelling needs by adding TPU film to ensure excellent stiffness and tensile strength, and adding adhesion coating process and silicon dioxide ceramic film evaporation process to prevent electrolyte penetration, compared with the existing swelling tape technology process based on coating process. It is more flexible, has higher production efficiency and processing precision, and therefore has obvious cost advantages.

[0035] 5. The utility model adopts a pressure-sensitive adhesive transfer coating process, which reduces the one-time heating coating process of the conventional process for producing swelling tapes, thereby reducing the probability of deformation and bubble problems of the swelling tape, improving product performance and providing quality assurance, and expanding the scope of application. It can meet the needs of products with different swelling rates and different mechanical properties, and can be used in home appliances, automobiles, machinery, instruments, batteries, decoration and other industries. Specifically, it can be used for gap filling in home appliances, automobiles, lithium batteries, instruments and various mechanical parts under specific environments.

[0036] Example 1

[0037] A multi-layer composite anti-wrinkle swelling tape made of a PET single-sided chemically treated substrate and having a TPU / PET interlayer peeling force of ≤8M / 20mm, comprising from outside to inside:

[0038] 1. A functional PET substrate layer, comprising a PET substrate layer coated with an adhesion-enhancing coating, wherein the adhesion-enhancing coating is coated on the lower surface of the PET film, the PET film thickness is 5 μm, the adhesion-enhancing coating coating dry weight is 0.05 g / ㎡, the solid content is 5%, and the thickness is 0.03 μm.

[0039] 2. Functional TPU film, with a thickness of 20μm. A vacuum-coated silicon dioxide coating is completed on the upper surface of the TPU film. This is a ceramic-type high-barrier coating with excellent chemical stability. Its purpose is to prevent the electrolyte from corroding the surface of the TPU substrate to ensure the peeling force between the composite film layers in the subsequent composite process. The TPU used is a single-sided chemically treated TPU substrate on the lower surface. The lower surface of the TPU substrate needs to be coated with a pressure-sensitive adhesive or hot-melt adhesive resin. The chemically treated layer is to ensure the peeling force of the coated pressure-sensitive adhesive layer. The upper surface of the TPU substrate is a coating.

[0040] 3. Solvent-free compounding: TPU and PET are compounded without solvents, and the PET substrate is coated with glue. The compounding strength tends to be stable after compounding at room temperature and natural aging at room temperature for 24 hours.

[0041] 4. Pressure-sensitive adhesive layer. The pressure-sensitive adhesive used in this embodiment is acrylic water-soluble pressure-sensitive adhesive resin, which is coated by a coating machine and dried in a drying oven to form a pressure-sensitive adhesive layer. This embodiment uses a pressure-sensitive adhesive coating machine to coat the release film with a pressure-sensitive adhesive resin, which is then dried to form an adhesive film, and then synchronously transferred to the lower surface of the PET substrate of the swelling tape. The thickness of the acrylic pressure-sensitive adhesive layer is 5 μm.

[0042] 5. Release film layer: In this embodiment, a release film with a thickness of 19 μm and a transparent PET substrate is selected, and its performance ensures that the multi-layer composite anti-wrinkle swelling tape can be completely peeled off.

[0043] Example 2

[0044] A multi-layer composite anti-wrinkle swelling tape made of a double-sided chemically treated PET substrate with a TPU / PET interlayer peeling force of ≥8N / 20mm. The double-sided chemically treated PET substrate is the best choice, which can increase the peeling force between the aluminum coating and the PET substrate, thereby producing a multi-layer composite anti-wrinkle swelling tape with high tensile strength.

[0045] The product structure of this utility model patent is PET (thickness 20μm and width 1280mm) + tackifying resin base coating (coating of polyethyleneimine aqueous solution with a thickness of 0.07μm) + silicon dioxide coating (thickness 75nm) + TPU film layer (thickness 5μm) + acrylic pressure-sensitive adhesive coating layer (thickness 5μm) + release film (thickness 30μm).

[0046] The coating width is 1230mm, the coating amount is 2.0g / ㎡, the thickness of the dry adhesive layer is 1.8μm, the temperature of the winding roller is set to 35±5℃, the aging temperature is room temperature or 35±5℃m, and the tension of the first and second unwinding shafts, the compounding shaft and the winding shaft is adjusted to achieve the best composite effect that the composite film after aging naturally hangs down without curling after opening. The advantage of this embodiment is that the composite strength between the various component layers of the product is higher, so when immersed in the electrolyte, it shows the advantages of appearance flatness, high temperature resistance, no bubble points, and strong peeling force between the layers. The product structure of this embodiment includes from the outside to the inside:

[0047] 1. Functional TPU substrate layer 1, double-surface chemically treated PET substrate, width 1280mm, thickness 20μm, wetting tension ≥52 dyne / inch. Swelling functional PET substrate layer 2, film thickness 5μm, coating width 1230mm, the lower surface of the film is coated with polyethyleneimine water-soluble adhesion coating by a coater, the coating control index is 4# viscosity cup 19±2s, and a six-stage drying oven heating method is adopted, with temperature settings of 40, 50, 60, 80, 70, 75℃, coater speed 7-12m / min, coater thickness 0.07μm, including antistatic agent, defoamer, thickener and leveling agent.

[0048] 2. The functional substrate PET is selected with a width of 1280mm, a thickness of 20μm, and a surface dish wetting tension ≥54 dyne / inch. A silicon dioxide coating is vacuum evaporated on its upper surface. The machine speed is set at 80m / min, and the coating thickness is 75μm. When winding, the coating faces outward and is hung for standby. The TPU film is used as the solvent-free composite adhesive substrate.

[0049] 3. For the solvent-free composite layer, a solvent-free composite machine with a maximum coating width of 1300mm*6 meters of conveyor belt is used. The glue is applied by three-roller transfer method with a coating width of 1230mm. A two-component polyurethane composite adhesive is used with a coating amount of 2.0g / ㎡ and a dry adhesive layer thickness of 1.8μm. The composite machine speed is 150m / min, and the composite roller temperature is set to 35±5℃. The tension of the first and second unwinding shafts and the tension of the composite shaft and the winding shaft are controlled. The composite film is Pengzheng. When placed vertically, it is considered that it droops without curling as the standard for a qualified composite effect. The composite strength is fixed after aging for 24 hours at room temperature.

[0050] 4. Pressure-sensitive adhesive layer 4: Use a coating machine to coat the upper surface of the release film substrate with an acrylic pressure-sensitive adhesive layer with a thickness of 8 μm.

[0051] The difference between Example 2 and Example 1: a PET substrate with a double-sided chemical coating layer is used. The substrate layer 1 described specifically is a TPU film 1 with a thickness of 20 μm and a double-surface polyurethane solvent-based chemical coating, which is the same as Example 1. The TPU substrate layer with swelling function is a composition of a TPU polymer resin film and a polyethyleneimine adhesion-enhancing coating, and has a thickness of 5+0.08 μm. The vacuum coating is an inorganic compound that has undergone a vacuum coating process and is combined with a chemical treatment layer (specifically a polyurethane primer) on a PET substrate. The thickness of the enhanced vacuum coating 3 is 75 nm, which is the same as Example 1.

[0052] The pressure-sensitive adhesive layer 4 is an acrylic pressure-sensitive adhesive layer with a thickness of 8 μm, which is formed on the surface of the vacuum coating layer 3 by using a transfer coating process. The coating process is the same as that of Example 1.

[0053] Example 3

[0054] The difference between this embodiment 3 and embodiments 1 and 2 is that PI substrate is used instead of PET substrate. The tensile strength and stiffness of the product have the same functions. Therefore, the detailed introduction of each layer and process is similar to that of embodiment 1 and will not be repeated here.

[0055] Comparative Example

[0056] This comparative example adopts the mainstream product structure of TPU / PE or EVA / PE on the market, with a standard product thickness of 44±2μm. The product does not have an additional PET as a skeleton or a support layer of the swelling material layer to increase the tensile strength and stiffness of the product, but adopts the method of adding titanium dioxide to the PE film or adding inorganic (glass microbeads) microbeads to solve the deformation and shrinkage of the swelling material. Due to the lack of high temperature resistant and high tensile strength PET or PI material substrates in the product structure, the deformation of the swelling tape is prone to cause tiny bubbles in the high temperature environment, which is the main problem affecting the life of the swelling tape at present, and this is the main defect in the product structure.

[0057] The above are only preferred embodiments of the present invention and are not intended to limit the protection scope of the present invention. Any modification, equivalent substitution or improvement within the spirit of the present invention are included in the scope of the claims of the present invention.

Claims

1. A multi-layer composite anti-wrinkle swelling tape, characterized in that: The multi-layer composite anti-wrinkle swelling tape comprises, in sequence, a substrate layer, an adhesion-promoting coating layer coated on the substrate layer, a barrier layer bonded to the adhesion-promoting coating layer, a TPU film vapor-deposited on the barrier layer, an acrylic pressure-sensitive adhesive layer bonded to the TPU film, and a release paper layer adhered to the acrylic pressure-sensitive adhesive layer, wherein the barrier layer is made of silicon dioxide.

2. The multi-layer composite anti-wrinkle swelling tape according to claim 1, characterized in that: The substrate layer is one of PET, PA, PI, PC, PS, PE, PP, and EVA.

3. The multi-layer composite anti-wrinkle swelling tape according to claim 1, characterized in that: The barrier layer is a silicon dioxide layer formed by vacuum evaporation.

4. The multi-layer composite anti-wrinkle swelling tape according to claim 1, characterized in that: The barrier layer is made by vacuum evaporation, and the evaporated material is a non-metallic oxide or sulfide that can play a barrier role to the electrolyte.

5. The multi-layer composite anti-wrinkle swelling tape according to claim 1, characterized in that: The adhesion-promoting coating is a water-based coating, and the water-based coating is made of polyethyleneimine or thermosetting polyurethane resin.

6. The multi-layer composite anti-wrinkle swelling tape according to claim 1, characterized in that: The pressure-sensitive adhesive layer is arranged on the substrate layer by transfer coating.

7. The multi-layer composite anti-wrinkle swelling tape according to claim 1, characterized in that: The pressure-sensitive adhesive layer is acrylic pressure-sensitive adhesive.

8. The multi-layer composite anti-wrinkle swelling tape according to claim 1, characterized in that: The adhesion promoting coating and the barrier layer are compounded together at room temperature and then aged at room temperature.